Performance comparison of encapsulated PCM PV/T, microchannel heat pipe PV/T and conventional PV/T systems. (1st January 2019) - Modjinou, Mawufemo; Ji, Jie; Yuan, Weiqi; Zhou, Fan; Holliday, Sarah; Waqas, Adeel; Zhao, Xudong
Abstract: This paper compares a novel macro-encapsulated phase change material (PCM) based solar photovoltaic thermal (PV/T) system and micro-channel heat pipes (MCHP) PV/T with a conventional PV/T. PV/Ts are vulnerable to the freezing-damages and get badly influenced by freezing weather. This problem occurs as a result of the poor performance and failure of the heat transfer system to prevent the circulating fluid from freezing. PCM and MCHP are essential heat and cold conditioning systems with a wide range of applications that can be used to optimize the performance of PV/T. Specifically, this article used PCM and MCHP to analyse the performance and optimisation options of the novel PV/T systems theoretically and numerically. Mathematical models were developed to predict the performance of the systems. The results revealed good agreements between the model simulation and experimental measurement with sufficient confidence. The results show that the combined daily average photothermal and electrical efficiency can reach 36.71%, 35.53% and 31.78% for the encapsulated PCM, MCHP and regular or conventional PV/T systems respectively. Our results showed that the macro-encapsulated PCM panels and MCHP prevented freezing of regular PV/T to some extent. Highlights: This paper compares macro-encapsulated PCM and MCHP PV/T with a regular PV/T. Detailed simulation models for the three (3) PV/T systems were presented. The transient performance of the three (3) PV/T systems was analyzed and discussed. The combined efficiencies of the three (3) PV/T have been calculated. The PCM and MCHP raised the performance and prevented freezing to some extent.